Review of the PEA Method for Space Charge Measurements on HVDC Cables and Mini-Cables - Giuseppe Rizzo; Pietro Romano; Antonino Imburgia; Guido Ala (Energies, 2019)
This review takes into account articles and standards published in recent years concerning the application of the Pulsed Electro Acoustic (PEA) method for space charge measurement on High Voltage Direct Current (HVDC) cables and mini-cables. Since the 80s, the PEA method has been implemented for space charge measurements on flat specimens in order to investigate space charge phenomena and to evaluate the ageing of dielectrics. In recent years, this technique has been adapted to cylindrical geometry. Several studies and experiments have been carried out on the use of the PEA method for full size cables and HVDC cable models. The experiments have been conducted using different arrangements of the measurement setup and focusing attention on different aspects of space charge phenomena. In this work, the importance of space charge measurement is highlighted and the state-of-the-art PEA method application to full size cables and mini-cables is described. The main aim of this paper is to offer a complete and current review of this technique. In addition, limits on the use of PEA method are examined and main possible directions of research are proposed in order to improve the applicability, reliability, and replicability of this method.